The role of gong ensemble music in shaping ritual in Sabah: A comparison between Dusunic and Bajau Sama’ cultures - Jacqueline Pugh-Kitingan (Research Institute for Languages and Cultures of Asia and Africa (ILCAA), Tokyo University of Foreign Studies, 2018)
While some ethnomusicologists have looked at the impact of music in shaping Southeast Asian societies, this chapter focuses on the impact or significance of music, especially gong ensemble music, in shaping traditional ritual ceremonies in Sabah. Those discussed here are major ceremonies specifically for resolving imbalance due to perceived conflict between the human and spiritual worlds. Among traditional cultures in Sabah, the east Malaysian state of northern Borneo, gongs are important both as items of wealth and as musical instruments. Every community has its characteristic gong ensemble which can also include one or two drums according to culture, and each village has at least one gong set, the gongs of which are individually owned. Sometimes a family will own a complete set of gongs for the music of their particular community. Gong ensembles are played on important social occasions, as well as in certain ritual contexts. The music announces and supports the event and accompanies dance. In ritual contexts, gong ensemble music is believed to be the medium through which the physical and spiritual worlds merge. It under-girds ritual processes and supports dancing that symbolises activities occurring in the unseen spiritual realms. This paper will discuss the ritual significance of gong ensemble music from selected cultures in Sabah, and compare and contrast world-views and performance practices between particular Dusunic groups, representing ancient indigenous land based cultures, and the east coast Sama-Bajau, representing regional maritime cultures. It will also briefly discuss reasons why such music may or may not be performed in non-ritual celebrations and in newer contexts of religious change.